Electoral Violence and Democratic Consolidation in Nigeria: Issues and Challenges - Harry, Deinibiteim M.; Kalagbor, Samuel B. (Advances in Social Sciences Research Journal, 2021)
The study examined the effects of electoral violence on the democratization efforts and democratic consolidation in Nigeria since the beginning of the Fourth Republic in 1999. The nation’s elections, at all levels of governance, are characterized by violence. Violence mar as high as 70 percent of Nigerian elections resulting in deaths, destruction of properties, maiming, etc. Successive governments have made frantic efforts to institutionalize and consolidate democracy in the country, embarking on various electoral reforms with little or no result with respect to curbing electoral violence. Thus, the main objective of this study is to show that the high rate of electoral violence witnessed over the years has weakened and discredited the democratic consolidation drive of the Nigerian state. The theoretical framework adopted in this study is the “State Fragility Theory”. However, the author’s modified version of “State Compromise Theory” was used to analyze the nature, character and reasons for electoral violence in Nigeria and its effects on the institutionalization of democracy in the country. The study used both primary and secondary data. The primary data were mainly drawn from mainly the authors’ observations during elections, over the years, while secondary data were drawn from existing literature on the subject matter. The study revealed that the pervasive violence at different elections has greatly discredited and emasculated democratic governance in the country. Violence has become both physical and cathartic. It manifests in form of wanton shooting by political thugs to intimidate voters and electoral officials, so as to snatch election materials, disruption of voting, vote suppression, cancellation and annulment of elections in opposition strongholds, etc. The paper concluded that, to ensure the consolidation of democracy in Nigeria, election management bodies must adopt an electoral system that drastically reduces congregation of people at a voting point(s) so as to reduce violence. Some of the recommendations are that election management bodies should deploy appropriate technology to reduce congregation of people at a voting point, transmission of results should be done electronically to minimize human involvement, contacts error and manipulations.